1999
DOI: 10.1046/j.1365-2249.1999.00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CR3 (CD11b/CD18)-dependent natural killer (NK) cell cytotoxicity by tumour target cell MHC class I molecules

Abstract: SUMMARYPhagocyte and NK cell CR3 functions as both an adhesion molecule and an iC3b receptor mediating cytotoxic responses to microorganisms. Cytotoxic activation of iC3b receptor function requires ligation of both a CD11b I-domain site for iC3b and a lectin site located in the C-terminus of CD11b. Because tumours lack the CR3-binding polysaccharides of bacteria and fungi, iC3b-opsonized tumours do not stimulate CR3-dependent cytotoxicity. Previous studies showed that NK cells could be induced to kill iC3b-ops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Indeed, NK cells can lyse tumor cells after the recruitment of complement receptor 3 (CR3) by iC3b, especially when MHC class I molecules are poorly expressed. 45 NeuT C tumor cells are susceptible to the activity of NK cells, as an inverse correlation exists between the expression levels of neuT protein and those of MHC class I molecules as well as other components of the antigen-processing machinery. 46 Moreover, signaling through the Her2/Her3 pathway in breast tumor cell lines has been shown to enhance their recognition by NK and T cells thanks to the killer cell lectin-like receptor subfamily K, member 1 (KLRK1, or NKG2D).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NK cells can lyse tumor cells after the recruitment of complement receptor 3 (CR3) by iC3b, especially when MHC class I molecules are poorly expressed. 45 NeuT C tumor cells are susceptible to the activity of NK cells, as an inverse correlation exists between the expression levels of neuT protein and those of MHC class I molecules as well as other components of the antigen-processing machinery. 46 Moreover, signaling through the Her2/Her3 pathway in breast tumor cell lines has been shown to enhance their recognition by NK and T cells thanks to the killer cell lectin-like receptor subfamily K, member 1 (KLRK1, or NKG2D).…”
Section: Discussionmentioning
confidence: 99%
“…Previously published in vitro experiments suggested that small molecular mass soluble ␤-glucans mediated neutrophil, M, and NK cell CR3-dependent cellular cytotoxicity of iC3b-opsonized tumors (25,33,34). Many of these small molecular mass soluble ␤-glucans demonstrated in vivo efficacy, but were observed to have very brief in vivo t 1/2 , thus requiring daily i.v.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is an adhesion molecule mediating the diapedesis of neutrophils through endothelium [1]. Secondly, being a complement receptor (CR3) it mediates and supports phagocytosis of pathogens and further regulates the degranulation response to microorganisms [1,[33][34][35]. However, it is important that cytotoxic agents from neutrophil granules are not released until neutrophils have migrated into the extracellular tissue to the site of infection.…”
Section: Discussionmentioning
confidence: 99%